Arguing to Learn
IX, 269 p.
Keywords: Arguing to Learn: Confronting Cognitions in Computer-Supported Collaborative Learning Environments focuses on how new pedagogical scenarios, task environments and communication tools within Computer-Supported Collaborative Learning (CSCL) environments can favour collaborative and productive confrontations of ideas, evidence, arguments and explanations, or arguing to learn. This book is the first that has assembled the work of internationally renowned scholars on argumentation-related CSCL research. All chapters present in-depth analyses of the processes by which the interactive confrontation of cognitions can lead to collaborative learning, on the basis of a wide variety of theoretical models, empirical data and Internet-based tools.